Diastereoselective synthesis of trifluoromethylated 1, 3-dioxanes by intramolecular oxa-Michael reaction. Issue 2 (29th November 2016) - Becerra-Figueroa, Liliana; Brun, Elodie; Mathieson, Michael; Farrugia, Louis J.; Wilson, Claire; Prunet, Joëlle; Gamba-Sánchez, Diego
Abstract : A rapid and simple method to access trifluoromethylated 1, 3-dioxanes by a sequence of addition/oxa-Michael reaction has been developed; the reaction proceeds smoothly with excellent stereoselectivity. Abstract : A highly diastereoselective synthesis of trifluoromethylated 1, 3-dioxanes is described. The reaction proceeds by an addition/oxa-Michael sequence and works efficiently under mild reaction conditions, with a good substrate scope and acceptable to good yields.